2021
DOI: 10.3390/ijms22136860
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NAMPT-Mediated NAD Salvage Pathway Contributes to Psoriasis Pathogenesis by Amplifying Epithelial Auto-Inflammatory Circuits

Abstract: Dysregulated cross-talk between immune cells and epithelial compartments is responsible for the onset and amplification of pathogenic auto-inflammatory circuits occurring in psoriasis. NAMPT-mediated NAD salvage pathway has been recently described as an immunometabolic route having inflammatory function in several disorders, including arthritis and inflammatory bowel diseases. To date, the role of NAD salvage pathway has not been explored in the skin of patients affected by psoriasis. Here, we show that NAD co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…In this capacity NAMPT triggers the activation of cells by binding to receptors 49 leading to the release of in ammatory factors and contributing to in ammation processes. Studies indicate that the modulation of NAD + metabolism by NAMPT enhances skin immunity responses 50,51 in conditions, like psoriasis. Another study suggest NAMPT's role in Crohn's disease 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In this capacity NAMPT triggers the activation of cells by binding to receptors 49 leading to the release of in ammatory factors and contributing to in ammation processes. Studies indicate that the modulation of NAD + metabolism by NAMPT enhances skin immunity responses 50,51 in conditions, like psoriasis. Another study suggest NAMPT's role in Crohn's disease 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin has nicotinamide phosphoribose transferase (Nampt) activity, the rate-limiting enzyme of the nicotinamide adenine dinucleotide (NAD) remedial synthesis pathway, and macrophages rely on the NAD remedial pathway to meet their energy requirements and maintain their proinflammatory phenotype, and visfatin promotes the release of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α from peripheral monocytes [17][18][19]. Interestingly, visfatin appears to have antiinflammatory [42][43][44] as well as pro-inflammatory effects [17][18][19][45][46][47][48]. In response to this seemingly contradictory result, the study by Sayers et al may give us some insight.…”
Section: Discussionmentioning
confidence: 99%
“…They found that depletion of NAD+ reduced PARP1/ARTD1 catalytic activity, suppressed the expression of IL-6, IL-1β, and TNF-α, and skewed monocytes/macrophages from pro-inflammatory towards anti-inflammatory phenotypes [ 56 ]. In the same line, reduction of NAMPT-derived NAD+ via pharmacological inhibition of NAMPT reduced the pathological changes in psoriasis [ 57 ] and atopic dermatitis [ 58 ] and diminished the expression of pro-inflammatory biomarkers.…”
Section: Parylation Macrophages and Chronic Inflammationmentioning
confidence: 99%
“…Activity Disease/Biological Process(s) PARP1/ARTD1 PARylation, MARylation, or non-catalytic activity Emphysema/Chronic lung inflammation [49,50] H. pylori infection [51] Colitis/Inflammatory bowel diseases [53,54,56] Psoriasis [57,66] Atopic dermatitis [58] Alcoholic liver injury [63] Chagas heart disease [69][70][71][72] PARP7/ARTD14 MARylation SARS-CoV-2 infection [23] Colitis/Inflammatory bowel diseases [53,54,56] PARP9/ARTD9 MARylation Pulmonary tuberculosis [83,84] RNA-viruses infections [85,86] Atherosclerosis/arterial inflammation [79,80] SARS-CoV-2 infection [117] PARP10/ARTD10 MARylation SARS-CoV-2 infection [23] Arboviruses infections [88] PARP12/ARTD12 MARylation Assembly and maintenance of stress granules [15] SARS-CoV-2 infection [23] PARP13/ARTD13 Non-catalytic activity Assembly and maintenance of stress granules [15] Atherosclerosis/arterial inflammation [79,80,90,91] Arboviruses infections [88,89] PARP15/ARTD7 MARylation Assembly and maintenance of stress granules [15] Arboviruses infections [88] PARG Hydrolysis (PAR) Assembly and maintenance of stress granules [15,98] Macrodomain 1 (nsp3) Hydrolysis (MAR) SARS-CoV-2 infection …”
Section: Enzymementioning
confidence: 99%